2010
DOI: 10.1007/s10671-010-9087-0
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity, self-concept, and school belonging: effects on school engagement

Abstract: This study examined the relationship of self-concept, school belonging, school engagement to school performance of Caucasian-and African-American students. The main purpose is to assess the ethnicity-based differences in these psycho-social constructs and to explore their differential relationship to school achievement in high-school students from different ethnic background. The data were collected through a survey questionnaire in three school divisions in the Southwest region of Virginia of the United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 51 publications
0
37
0
5
Order By: Relevance
“…When measured concurrently, students’ perceived school belonging and indices of achievement are positively related (Anderman, 2003; Goodenow, 1993; Singh, Chang, & Dika, 2010). Longitudinal studies have also documented associations between middle school students’ school belonging and academic engagement and achievement (Wang & Holcombe, 2010).…”
Section: School Belonging During Middle Schoolmentioning
confidence: 99%
“…When measured concurrently, students’ perceived school belonging and indices of achievement are positively related (Anderman, 2003; Goodenow, 1993; Singh, Chang, & Dika, 2010). Longitudinal studies have also documented associations between middle school students’ school belonging and academic engagement and achievement (Wang & Holcombe, 2010).…”
Section: School Belonging During Middle Schoolmentioning
confidence: 99%
“…USA researchers have demonstrated that academic self-concept generally has a positive direct relationship with achievement (Marsh and Martin, 2011) or reciprocal relationship with achievement (Guay et al, 2003). It is important to point out though that this relationship does not hold true for all ethnic groups as school environments play a role in moderating this relationship for African Americans high school students (Mboya, 1988;Singh et al, 2010). Nevertheless, the findings from this study demonstrate that is does hold true for Afro-Caribbean students in England.…”
Section: Discussionmentioning
confidence: 54%
“…Gonzalez-Pienda et al [68] used data for 503 12-to 18-year-old adolescents, and reported that their self-concept was statistically related to their academic achievement. Singh et al [69] collected data through a survey in three school divisions in the Southwest region of Virginia, USA. There was a slight association between school outcomes (self-reported grades) and self-concept (at least for White students), and a slightly stronger link between a student's school outcomes and their sense of school belonging.…”
Section: Individual Motivationmentioning
confidence: 99%